Navigating the midcareer plateau (O'Reilly Media, 2019)
"Drawing on her experience supporting engineers and managers through career growth in environments ranging from large company environments to startups, Uma Chingunde (Stripe) offers strategies to think about careers at this stage. She addresses some questions such as, How do you think of your career goal outside of the usual career ladders? How do these change as you get more senior? What are traditional versus nontraditional IC and manager paths you can explore? How do you think about the engineer versus manager track? What are some variations on the above for underrepresented groups?"--Resource description page